Paul M. Weyrich scrapbooks - Weyrich, Paul M.
Correspondence, minutes of meetings, speeches, writings, media scripts, agenda, rail transit records, church records, family papers, news releases, newsletters, clippings, posters, flyers, political cartoons, photographs, and other papers pertaining chiefly to Weyrich's political and religious activities. Reflects his leading role in the conservative movement, especially the New Right, building a coalition of Catholic and evangelical Protestants, conservative activists, and the Republican Party. Documents his role as co-founder and president of the Heritage Foundation (Washington, D.C.), Free Congress Research and Education Foundation, and Krieble Institute; career as a radio and television journalist and columnist; work for Senators Gordon Allott and Carl T. Curtis; and involvement in the Roman Catholic church and the Holy Transfiguration Melkite Greek-Catholic Church, McLean, Va. Subjects include Weyrich's advocacy of limited government and of religion and morality in public and private life, and his opposition to liberal issues including abortion, feminism, gay rights, and union rights. Includes material pertaining to his childhood in Racine, Wis.; years as a student at the University of Wisconsin, Madison, Wis.; and interest in railroads and service on the Amtrak Board of Directors and Amtrak Reform Council.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Political activist and commentator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allott, Gordon, -- 1907-1989.; Curtis, Carl T. -- 1905-2000.; Weyrich family; Wyrick family; Amtrak. -- Board of Directors; Amtrak Reform Council (U.S.); Catholic Church; Catholic Church -- Byzantine rite, Melchite; Free Congress Research and Education Foundation; Heritage Foundation (Washington, D.C.); Holy Transfiguration Melkite Greek-Catholic Church; Krieble Institute; Republican Party (U.S. : 1854- ); University of Wisconsin--Madison.; Abortion; Broadcast journalism -- United States; Christianity and politics -- United States; Conservatism -- United States; Conservatism -- United States -- Religious aspects; Evangelicalism -- United States; Federal government -- United States; Feminism; Gay rights; Journalism -- United States; Labor unions; Radio journalism -- United States; Railroads -- United States; Social values -- United States; Racine (Wis.) -- Social life and customs; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-; United States -- Religion; United States -- Social conditions -- 1945-; Commentators; Political activists